Stationary average-tracking problem of unmatched constant reference signals based on delayed-state feedback. Issue 13 (3rd October 2021) - Liu, Cheng-Lin; Li, He; Shan, Liang
Abstract : Stationary average-tracking problems of unmatched constant reference signals are investigated for first-order multi-agent systems, and an integral-type average-tracking algorithm with delayed-state feedback is constructed. With identical communication delays and different introduced self-delays, sufficient conditions are obtained for the agents converging to the average-value of unmatched reference signals asymptotically by using the frequency-domain analysis method. To our delight, introducing delayed-state feedback improves the robustness to communication delay and unmatched reference signals. Simulation results show the effectiveness of our proposed algorithm.